2015
DOI: 10.1007/s00005-015-0342-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Myeloid-Derived Suppressor Cells in Inflammatory Diseases

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of cells involved in immune regulation. This population subdivides into granulocytic MDSCs and monocytic MDSCs, which regulate immune responses via the production of various molecules including reactive oxygen species, nitric oxide, arginase-1, interleukin-10, and transforming growth factor-β. Most studies of MDSCs focused on their role in tumors. MDSCs protect tumor cells from immune responses, and thus the frequency of MDSCs associates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 176 publications
0
35
0
Order By: Relevance
“…Immunosuppressive cells have a fundamental role in the suppression of detrimental innate and adaptive immune responses and in the maintenance of immune self-tolerance. Overall, the activation of immunosuppressive cells, such as MDSCs and Tregs, has beneficial effects since it results in the resolution of acute inflammatory responses and the suppression of excessive inflammatory disorders, e.g., sepsis, autoimmune diseases, and transplantation [110,112,186]. However, in chronic inflammatory conditions, e.g.…”
Section: Chronic Immunosuppression Disturbs the Homeostasis Of Tissuesmentioning
confidence: 99%
“…Immunosuppressive cells have a fundamental role in the suppression of detrimental innate and adaptive immune responses and in the maintenance of immune self-tolerance. Overall, the activation of immunosuppressive cells, such as MDSCs and Tregs, has beneficial effects since it results in the resolution of acute inflammatory responses and the suppression of excessive inflammatory disorders, e.g., sepsis, autoimmune diseases, and transplantation [110,112,186]. However, in chronic inflammatory conditions, e.g.…”
Section: Chronic Immunosuppression Disturbs the Homeostasis Of Tissuesmentioning
confidence: 99%
“…The first process is the expansion induced by various cytokines and growth factors produced in response to chronic stimulation, which involves factors like IL-6 and VEGF, and signaling pathways such as STAT3 and NF- κ B, which prevents maturation of myeloid cells. Then, a second activating signal provided by proinflammatory molecules to drive upregulation of arginase and iNOS and production of immune suppressive cytokines is required for their activation [130, 131]. In addition to above proposed pathways, it is reported that activated human HSCs during chronic inflammation induced mature peripheral blood monocytes into MDSCs, and, subsequently, excessive liver injury might be prevented by local induction of MDSCs.…”
Section: Immune Suppression: a Potential Linkage Of Oxidative Strementioning
confidence: 99%
“…In addition to above proposed pathways, it is reported that activated human HSCs during chronic inflammation induced mature peripheral blood monocytes into MDSCs, and, subsequently, excessive liver injury might be prevented by local induction of MDSCs. However, of note, in liver cancer patients, the expansion of HSC-induced MDSCs plays an opposite role to facilitate tumor growth by immune suppression [130, 131, 136]. …”
Section: Immune Suppression: a Potential Linkage Of Oxidative Strementioning
confidence: 99%
“…In addition, because MDSCs are known to mediate T cell suppression through numerous genes, including ARG1, Nox2, IDO1, iNOS, PD-L1, HIF-1α, IL-4Rα, and MyD88, which reportedly involved in MDSC biology [27], we compared the expression levels of these genes by qRT-PCR in G-MDSCs and M-MDSCs isolated from PBMCs of 34 patients obtained at engraftment (Supplementary Figure S2). Among the target genes, ARG1 and Nox2 were significantly increased in G-MDSCs, whereas PD-L1 and HIF-1α were up-regulated in M-MDSCs.…”
Section: Cytokines and Known Factors Related To Mdsc Suppressive Actimentioning
confidence: 99%